Enhanced Information Flow From Cerebellum to Secondary Visual Cortices Leads to Better Surgery Outcome in Degenerative Cervical Myelopathy Patients: A Stochastic Dynamic Causal Modeling Study With Functional Magnetic Resonance Imaging - Zhao, Rui; Song, Yingchao; Guo, Xing; Yang, Xiaotian; Sun, Haoran; Chen, Xukang; Liang, Meng; Xue, Yuan (Frontiers in Human Neuroscience, 2021)
Degenerative cervical myelopathy (DCM) damages the spinal cord resulting in long-term neurological impairment including motor and visual deficits. Given that visual feedback is crucial in guiding movements, visual disorder may be a cause of motor deficits in DCM patients. It has been shown that increased functional connectivity between secondary visual cortices and cerebellum, which are functionally related to the visually guided movements, was correlated with motor function in DCM patients. One possible explanation is that the information integration between these regions was increased to compensate for impaired visual acuity in DCM patients and resulted in better visual feedback during motor function. However, direct evidence supporting this hypothesis is lacking. To test this hypothesis and explore in more detail the information flow within the “visual-cerebellum” system, we measured the effective connectivity (EC) among the “visual-cerebellum system” via dynamic causal modeling and then tested the relationship between the EC and visual ability in DCM patients. Further, multivariate pattern analysis was performed to detect the relationship between the pattern of EC and motor function in DCM patients. We found (1) significant increases of the bidirectional connections between bilateral secondary visual cortices and cerebellum in DCM patients; (2) the increased self-connection of cerebellum was positively correlated with the impaired visual acuity in patients; (3) the amplitude of effectivity from cerebellum to secondary visual cortices were positively correlated with better visual recovery following spinal cord decompression surgery; (4) and the pattern of effective connectivity among visual-cerebellum system could be used to predict the preoperative motor function. To conclude, this study provided direct evidence that the increased information integration within “visual-cerebellum system” compensated for visual impairments, which might have importance for sustaining better motor function in DCM patients.